Gene expression profiling identifies the zinc-finger protein Charlatan as a regulator of intestinal stem cells in Drosophila. - Amcheslavsky, A.; Nie, Y.; Li, Q.; He, F.; Tsuda, L.; Markstein, M.; Ip, Y.T. (Development, 2014)
Intestinal stem cells (ISCs) in the adult Drosophila midgut can respond to tissue damage and support repair. We used genetic manipulation to increase the number of ISC-like cells in the adult midgut and performed gene expression profiling to identify potential ISC regulators. A detailed analysis of one of these potential regulators, the zinc-finger protein Charlatan, was carried out. MARCM clonal analysis and RNAi in precursor cells showed that loss of Chn function caused severe ISC division defects, including loss of EdU incorporation, phosphorylated histone 3 staining and expression of the mitotic protein Cdc2. Loss of Charlatan also led to a much reduced histone acetylation staining in precursor cells. Both the histone acetylation and ISC division defects could be rescued by the simultaneous decrease of the Histone Deacetylase 2. The overexpression of Charlatan blocked differentiation reversibly, but loss of Charlatan did not lead to automatic differentiation. The results together suggest that Charlatan does not simply act as an anti-differentiation factor but instead functions to maintain a chromatin structure that is compatible with stem cell properties, including proliferation.